State of the ant: how broad is our recent knowledge of Neotropical ant behavior? - Quesada-Hidalgo, Rosannette; González, Yorlenis; Gálvez, Dumas; Marting, Peter R.; Castillo-Pimentel, Armando; Aguilar, Jane; Cox, Stephen; Smith, Carrie; Amador-Vargas, Sabrina (Frontiers in Insect Science, 2025)
Over the years, most scholarly published papers have studied vertebrates, despite invertebrates’ higher species diversity and number of individuals. This has led to an inaccurate representation of global biodiversity patterns in scientific publications. Furthermore, the bias for studying vertebrates is also evident when comparing studies conducted in the tropics vs. temperate zones. We investigated whether similar taxonomic and geographical biases are maintained in recent years when studying the behavior of Neotropical ants. We searched for papers published between 2015 and 2022 with the words “ant” OR “ants” OR formicidae; tropic* OR neotropic* and behav* AND tropic* OR neotropic*. We found that recently published papers studying ants cover only ~10% of the Neotropical ant species, with a primary focus on economically damaging and/or invasive ants. Our results revealed that studies on ant behavior in the Neotropics are dominated by four species, which represent less than 0.15% of the ant species in the Neotropics, and that 50% of the focal species were mentioned only once or twice in studies regarding behavior. Moreover, recent ant behavior studies cover only approximately 8% of the Neotropical ant biodiversity. We found that the Neotropical countries where most ants have been collected for behavioral studies are Brazil, Panama, and Costa Rica. In contrast, other Central American countries are absent from the recent ant literature. Our results reveal concerning patterns of taxonomic and geographical inequity in the study of Neotropical ant behavior, despite its potential role in managing ant invasions and ensuring effective conservation measures. We highlight the need to broaden behavioral studies in the Neotropics and urge researchers to investigate relatively unknown ant species, and include understudied countries with limited scientific resources to fill this critical gap in current ant research.